IMPLEMENTASI ALGORITME TWOFISH UNTUK MELINDUNGI LAPORAN KEUANGAN BIMBA AIUEO - Siswanto, Siswanto; Akbar, Muhammad; Anif, Muhammad; Saputro, Ari; Subandi, Subandi; Prasetyo, Basuki Hari (SKANIKA: Sistem Komputer dan Teknik Informatika, 2023)
The problem with Bimba AIUEO is that there are frequent changes in financial reports by staff at Bimba AIUEO from both Bimba and Bimbel. The purpose of this research is to build an application to protect Bimba AIUEO's financial statements using the twofish cryptographic algorithm. The results of the application trial showed that the ciphertext that had been encrypted had changed in size by 1.81%, the plaintext that had been decrypted was an accuracy rate of 100% and there was no damage to the contents of the file. The test results of 26 UAT respondents 89.1% agreed that the entire implementation of the twofish algorithm can be used by Bimba AIUEO employees to easily protect financial reports